INNOVATIVE APPROACH TO DIAGNOSTICS OF TECHNICAL SYSTEMS OF MILL PQF OF TUBE PRODUCTION - A. N. Katsin (Литьë и металлургия)
Innovative approach to diagnostics of the technical systems of the mill PQF of pipe production is considered.